2016
DOI: 10.1007/s40596-016-0647-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of Electronic Resources for Psychiatry Clerkship Learning: A Medical Student Survey

Abstract: The authors' results suggest that a demand exists for high-quality electronic and portable learning tools that are relevant to medical student education in psychiatry. Psychiatry educators are usefully positioned to be involved in the development of such resources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 7 publications
2
9
0
Order By: Relevance
“…We also surveyed residents on the possible barriers in implementing mobile technology in clinical practice through multiple choice as well as an option to write in barriers that were not included in the available choices. Barriers provided were based on a previous study that identified barriers in using electronic resources among medical students on their psychiatry clerkship [ 3 ]. The survey questions have been listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also surveyed residents on the possible barriers in implementing mobile technology in clinical practice through multiple choice as well as an option to write in barriers that were not included in the available choices. Barriers provided were based on a previous study that identified barriers in using electronic resources among medical students on their psychiatry clerkship [ 3 ]. The survey questions have been listed in Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…The authors suggest that teaching about nontraditional sources may enhance the current curriculum. This was underscored by another survey of 62 psychiatry residents which showed that 68% primarily use online resources for education rather than printed materials [ 3 ]. Given that majority of the population use mobile apps to access digital media, it seems likely that medical students and residents also access clinical resources via their phones and apps [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is a reported appetite for the exploration of new educational models that involve interactive learning by integrating electronic/portable learning tools that meet modern learners in their realm of technological familiarity and ondemand access. For example, medical students who completed a psychiatry clerkship reported high use of electronic resources on an array of devices for learning and even indicated preference for such formats, compared to printed resources (10). Moreover, web-based instruction formats have the potential of tracking learning outcomes or even patient care on a longitudinal scale (11), and remote, interactive learning experiences, with expert faculty as moderators, can compensate for limited local expertise in certain topics (12).…”
Section: Strategies For Incorporating Active Learning Modelsmentioning
confidence: 99%
“…There is a clear unmet need for high-quality web-based resources in psychiatry education. Survey research involving medical students rotating on psychiatry clerkships suggests that 90% want more educational smartphone apps [ 3 ] and that only a minority currently use printed material like text books or review books [ 4 ]. Increasingly, medical students are utilizing question banks [ 5 ] and are even creating their own in some instances [ 6 ].…”
Section: Introductionmentioning
confidence: 99%